Stories of change: How Rwanda created an enabling environment for reducing malnutrition (P22-011-19) - Iruhiriye, Elyse; Olney, Deanna K.; Heckert, Jessica; Ramani, Gayathri V.; Frongillo, Edward A.; Niyongira, Emmanuel (Oxford University Press, 2019)
Eliminating malnutrition is on many countries’ political agendas but knowledge of how enabling environments are created and used is needed. We assessed the drivers of change in stunting reduction among children <5 y of age in Rwanda and contributors to differential reduction over 10–25 y.